Implikasi Modal Sosial Dalam Sistem Pembiayaan Multiguna Tanpa Agunan Di Baitul Mal Wat Tamwil - Bahrina Almas (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study aims to determine the implications of social capital in the multipurpose financing system without collateral at Baitul Maal wat Tamwil. The research method used is qualitative with a phenomenological descriptive approach. The results show that the existence of social capital, namely trust, shared values, norms and networks supports the implementation of multipurpose financing without collateral. The existence of interactions and good relationships between prospective customers and Baitul Maal wat Tamwil customers who become mediators creates a sense of trust for Baitul Maal wat Tamwil to provide financing. Likewise for customers who directly apply to Baitul Maal wat Tamwil, because they have previously been members of Baitul Maal wat Tamwil. Interaction and good relations create a sense of trust with each other bound by shared values and norms that have been agreed. This makes it easier for Baitul Maal wat Tamwil to provide financing. The multipurpose financing system without collateral that is supported by social capital between the Baitul Maal wat Tamwil and prospective financing customers embodies the ta'awun principle as the basis for Baitul Maal wat Tamwil's foothold in the mission of making it easier for lower-line communities to gain access to business capital.